1999
DOI: 10.1677/joe.0.1610357
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet cell survival following islet isolation: the role of cellular interactions in the pancreas

Abstract: The purpose of this study was to characterize the trophic effect of pancreatic duct cells on the islets of Langerhans. Ductal epithelium and islets were isolated from hamster pancreata. In addition, duct-conditioned medium (DCM) was prepared from primary duct cultures that had been passaged twice to remove other cellular elements. Three experimental groups were then established: Group 1, 100 islets alone; Group 2, 100 islets+80 duct fragments; and Group 3, 100 islets in 25% DCM. All tissues were embedded in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 46 publications
3
85
0
Order By: Relevance
“…Surrounding acinar and ductal cells are considered to be the source of important islet growth and regulatory factors, and the loss of their influences following islet isolation and culture may result in disordered beta cell function [18,19]. In the present investigation we sought to determine whether appropriate glucose signalling and insulin secretion could be restored in culture by re-establishing cellular interactions between islets and non-endocrine components of the human pancreas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surrounding acinar and ductal cells are considered to be the source of important islet growth and regulatory factors, and the loss of their influences following islet isolation and culture may result in disordered beta cell function [18,19]. In the present investigation we sought to determine whether appropriate glucose signalling and insulin secretion could be restored in culture by re-establishing cellular interactions between islets and non-endocrine components of the human pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…In the present investigation we sought to determine whether appropriate glucose signalling and insulin secretion could be restored in culture by re-establishing cellular interactions between islets and non-endocrine components of the human pancreas. Specifically, we aimed to re-introduce the influences exerted by pancreatic ductal epithelial cells (DECs), which are considered to be a potential source of trophic factors [19], ECM components [20] and beta cell progenitors [21] thought to contribute to sustained graft survival following islet transplantation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors play a role in early beta cell damage and death after transplantation, including islet injury during isolation [4,5], technical problems in the transplantation process [6], inadequate mass of islet tissue [7], hypoxia [8], exposure to the recipient hyperglycaemia [9], absence of survival factors present in the non-endocrine pancreas [10], or disruption of islet cellular connections to extracellular matrix [11]. In addition, non-specific inflammation at the grafted site, involving the expression of pro-inflammatory cytokines, is considered to play a role in early graft failure [4,5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The culture medium was changed every second day as previously described. 5 Note that, for in vivo experiments, the time in culture (in CMRL) was limited to 2 days, the islets being transplanted 24 h after encapsulation and 48 h after isolation, which corresponds to what would be done in clinical applications. TM4-IGF-II and TM4-GFP cells were cultured in DMEM/F12 supplemented by serum until co-encapsulation with islets, then cultured for 24 h in CMRL until transplantation.…”
Section: Islet Isolationmentioning
confidence: 99%
“…5 We have investigated the use of IGF-II in a transplantation setting. 6 In vitro studies showed that IGF-II prevents the apoptosis and necrosis of microencapsulated mouse islet cells in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%